A framework for SLA assurance in cloud computing - Hammadi, Adil; Hussain, Omar (2012)
One of the challenges of cloud computing is SLA assurance. On-demand and self-serve nature of cloud requires ascertaining real-time QoS assurance to meet SLA specifications of the consumer. A third-party service provider could be used to provide on demand QoS assessment service. We propose a SLA monitoring framework to address the real-time QoS assessment issue. The framework consists of two modules namely, reputation assessment module and transactional risk assessment module. Third-party service provider equipped with such assessment modules can provide real-time assessment for consumer's informed decision making to continue using a service or to migrate to another service provider in the case of service degradation. © 2012 IEEE.